2017
DOI: 10.1038/s41467-017-01877-7
|View full text |Cite
|
Sign up to set email alerts
|

NSD1- and NSD2-damaging mutations define a subset of laryngeal tumors with favorable prognosis

Abstract: Squamous cell carcinomas of the head and neck (SCCHN) affect anatomical sites including the oral cavity, nasal cavity, pharynx, and larynx. Laryngeal cancers are characterized by high recurrence and poor overall survival, and currently lack robust molecular prognostic biomarkers for treatment stratification. Using an algorithm for integrative clustering that simultaneously assesses gene expression, somatic mutation, copy number variation, and methylation, we for the first time identify laryngeal cancer subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 60 publications
(78 reference statements)
4
47
0
Order By: Relevance
“…Recently, Peri et al reported that NSD1 mutation status predicted improved outcomes in laryngeal cancer using TCGA data; however, they did not identify a difference in prognosis in HPV-negative tumors in other head and neck subsites (12). That study did not integrate definitive viral transcript identification to classify tumor HPV status and instead relied on p16 and in situ hybridization testing, which was carried out on only a subset of cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Peri et al reported that NSD1 mutation status predicted improved outcomes in laryngeal cancer using TCGA data; however, they did not identify a difference in prognosis in HPV-negative tumors in other head and neck subsites (12). That study did not integrate definitive viral transcript identification to classify tumor HPV status and instead relied on p16 and in situ hybridization testing, which was carried out on only a subset of cases.…”
Section: Discussionmentioning
confidence: 98%
“…Targeted sequencing of NSD1 in an independent cohort of 77 oral cavity cancers also demonstrated improved overall survival for patients with NSD1 mutations in a multivariable survival model (P < 0.05, Figure 2B and Supplemental Table 7). We carried out a meta-analysis of 4 available data sets, including TCGA data set, Bui et al (11), Peri et al (12), and our validation cohort, comparing survival by NSD1 mutation status. The pooled estimate for these studies demonstrated strong evidence for improved overall survival for patients with NSD1-mutant tumors compared with patients with WT tumors (Figure 3, HR 0.44; 95% CI, 0.30-0.65; P < 0.0001).…”
Section: And Supplementalmentioning
confidence: 99%
“…H3K36me2 methyltransferase NSD1 is a modulator of PRC2 function and demarcates H3K27me2 and H3K27me3 domains in ESCs [ 123 ]. NSD1 inactivating mutations define a hypomethylated subtype in different cancer types such as head and neck squamous cell carcinoma (HNSC) and lung squamous cell carcinoma (LUSC) [ 124 126 ]. This subtype is also characterized by low T cell infiltration into the tumor microenvironment, suggesting an identification of this subtype prior to immunotherapy [ 125 ].…”
Section: Main Bodymentioning
confidence: 99%
“…NSD1 is a histone methyltransferase previously reported to be significantly altered within HPV– HNSCC . This putative tumor‐suppressor gene is correlated with significantly increased patient survival when the mutation is present; this is possibly related to a known strong association with genome‐wide hypomethylation and corresponding platinum sensitivity …”
Section: Resultsmentioning
confidence: 99%
“…4 This putative tumor-suppressor gene is correlated with significantly increased patient survival when the mutation is present; this is possibly related to a known strong association with genome-wide hypomethylation and corresponding platinum sensitivity. 21,22 Mutations of the tumor suppressor CREBBP and its closely related paralogue EP300 have not been previously identified in genome-wide studies of HPV+ HNSCC. Within the TCGA analysis, EP300 was the third most altered gene at 13% (6 of 46 tumors).…”
Section: Chromatin Regulators Are Significantly Mutated Within Hpv+ Omentioning
confidence: 99%